2014
DOI: 10.1002/mop.28783
|View full text |Cite
|
Sign up to set email alerts
|

A compact novel CPW‐fed antenna with square spiral‐patch for multiband applications

Abstract: A compact novel coplanar waveguide‐fed antenna with square spiral‐patch for multiband applications is presented. The antenna consists of a square‐spiral patch with two L‐shape strips. With subjoin square spiral the number of frequency resonance is increasing. Also by introducing two L‐shaped strips in the inside of square spiral, much wider impedance bandwidth can be produced, especially at the higher bands. The operating frequencies of the proposed antenna are 2.62/3.40/4.42/5.92/8.32 GHz. Some key parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…Recently, the development of ultra‐wideband (UWB) antennas enabling high data transmission rates and low power consumption, and simple hardware configuration in communication application has received attention . The Federal communication commission (FCC) allocated the frequency band 3.1–10.6 GHz for commercial UWB systems in 2002 . Despite the approval of the FCC for the UWB to operate 3.1–10.6 GHz, it may be necessary to avoid potential interferences with other existing communication systems, such as Worldwide Interoperability for the Microwave Access (WiMAX) operating at 3.3–3.6 GHz; Wireless Local Area Network (WLAN) is operated at 5.15–5.825 GHz .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the development of ultra‐wideband (UWB) antennas enabling high data transmission rates and low power consumption, and simple hardware configuration in communication application has received attention . The Federal communication commission (FCC) allocated the frequency band 3.1–10.6 GHz for commercial UWB systems in 2002 . Despite the approval of the FCC for the UWB to operate 3.1–10.6 GHz, it may be necessary to avoid potential interferences with other existing communication systems, such as Worldwide Interoperability for the Microwave Access (WiMAX) operating at 3.3–3.6 GHz; Wireless Local Area Network (WLAN) is operated at 5.15–5.825 GHz .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, UWB antenna with notched characteristics at these frequency bands is required. The conventional methods are cutting a slot (U‐shaped, arc shaped, T‐shaped slot) on the patch . Inserting a slit on the patch , another way is putting parasitic elements as filters to reject the electromagnetic interference (EMI).…”
Section: Introductionmentioning
confidence: 99%
“…A coplanar waveguide (CPW)-fed dual band monopole antenna is proposed in [4], and the resonance location can be altered by changing the embedded slots at the radiating patch. In [5], a square spiral-patch is presented for multiband applications. The design of a dual-band dipole antenna loaded with U-shaped slots is given in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the antennas in [1][2][3][4][5][6][7][8][9][10][11][12], our proposed antenna configuration not only achieves the triple bands simultaneously, but also has a rather simple and smaller structure which is easy to fabricate with low cost. What is more, our proposed antenna configuration also allows for the independent adjustment of each operating bands within certain limits, which is an important aspect for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In modern wireless communication systems, multiband antenna has been playing a very important role for wireless service requirements. Wireless local area network (WLAN) and worldwide interoperability for microwave access (WiMAX) have been widely applied in mobile devices, such as handheld computers and intelligent phones [2]. Also many efforts in UWB antenna fields have been reported that more descriptions come in [3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%